GOLDEN AGE OF AMERICAN LITERATURE - Maxmudova Madina; G. Isroiljon qizi (TADQIQOTLAR, 2025)
Abstract: The Golden Age of American Literature, spanning the 1830s to the Civil War, signifies the moment when American writing achieved cultural independence and intellectual refinement. In this period, authors examined democracy, personal freedom, spirituality, and moral duty while shaping a distinct national voice separate from European influence. Writers such as Emerson, Thoreau, Hawthorne, Melville, and Whitman introduced innovative forms and deep philosophical ideas that explored human nature, society, and personal integrity. Their legacy established the core of American literary tradition and continues to guide modern thought through an emphasis on inner truth, ethical awareness, and imaginative expression.